Ads, fads, and consumer culture : advertising's impact on American character and society - Berger, Arthur Asa, 1933- (Lanham : Rowman & Littlefield Publishers, 2011)
"Now in its fourth edition, Ads, Fads, and Consumer Culture deals with the impact of advertising upon American character and culture. It offers a definition of advertising, explains the way advertising agencies work, discusses the functions of advertising, and provides a psycho-cultural perspective on advertising. Among the topics it deals with are the role of brands in selling products and the problem of self-alienation and its relation to consumption. It also analyzes consumer cultures, places advertising in the communication process, and considers the use of sexuality in advertising, political advertising, and marketing theory. The marketing discussion deals with the Values and Lifestyle Typology (VALS) and the Claritas typology. The chapters analyzing print advertisements and television commercials are distinctive features of the book. For print advertising, it provides a list of topics to consider in analyzing print advertising and then provides a detailed analysis of a fascinating Fidji perfume advertisement that shows a Polynesian woman with a snake around her neck. It provides a semiotic, psychoanalytic, sociological, Marxist, mythic, and Feminist analysis of this advertisement. For television commercials, it analyzes the famous Macintosh "1984" commercials in a number of different ways as well. In the last chapter it speculates about the role of advertising in selling drugs to people, children and advertising, and the problems advertising agencies have in getting people's attention. It also offers a glossary to terms used in the book and an annotated bibliography." --Publisher's website.
10. Where next? -- Drug advertising -- Children and advertising -- Battling for people's attention -- Cell phones, social media, and advertising.
Includes bibliographical references (p. 219-223) and index.
Keywords: Advertising -- United States; Popular culture -- United States; Consumer education -- United States